You Mean Nothing Compared to AI: Tinjauan Etis-Teologis terhadap PHK Massal Akibat dari Implementasi AI - Sihombing, Eleazar H. F. (Jurnal Teologi Kontekstual Indonesia, 2025)
The implementation of artificial intelligence (AI) in various industrial sectors has caused tension between technological efficiency and worker dignity. This study aims to analyse the practice of layoffs due to AI implementation from an ethical-theological perspective. This research uses a qualitative-interpretive approach by examining Catholic Church documents, the Encyclical Laborem Exercens, and Christian Work Ethics from Martin Luther as a theoretical basis. The results of the study show that layoff practices driven by profit alone contradict the principle of human dignity as a subject of work and work as a divine calling. To ensure that technology does not conflict with human dignity, the adoption of AI must be accompanied by fair transition regulations, retraining, and ethical awareness among stakeholders. The final section of this study provides recommendations to ensure a fair transition for workers and companies, as well as the active role of the church in voicing the true prophetic voice.